Sowing Technology of Silver Fir (Abies pindrow) Seed in Nursery - Singh, Ombir (Indian Forester, 1998)
To find out the optimum sowing method of Silver fir (Abies pindrow) an experiment was conducted. The results revealed that line sowing in 4 cm and 6 cm wide strips is better than those seeds sown in 2 cm wide strips and broadcast sowing.